Calculation of Transient Potential Rise on the Wind Turbine Struck by Lightning - Zhang Xiaoqing (The Scientific World Journal)
A circuit model is proposed in this paper for calculating the transient potential rise on the wind turbine struck by lightning. The model integrates the blade, sliding contact site, and tower and grounding system of the wind turbine into an equivalent circuit. The lightning current path from the attachment point to the ground can be fully described by the equivalent circuit. The transient potential responses are obtained in the different positions on the wind turbine by solving the circuit equations. In order to check the validity of the model, the laboratory measurement is made with a reduced-scale wind turbine. The measured potential waveform is compared with the calculated one and a better agreement is shown between them. The practical applicability of the model is also examined by a numerical example of a 2 MW Chinese-built wind turbine.